Study protocol: analysis of regional lung health policies and stakeholders in Africa - Claire Jensen; Emma Heneine; Brenda Mungai; Violet Murunga; Hleziwe Hara; Rose Oronje; Angela Obasi; Bertie Squire; Eliya Zulu; On behalf of The IMPALA Consortium (BMC, 2020)
Abstract Background Lung health is a critical area for research in sub-Saharan Africa. The International Multidisciplinary Programme to Address Lung Health and TB in Africa (IMPALA) is a collaborative programme that seeks to fill evidence gaps to address high-burden lung health issues in Africa. In order to generate demand for and facilitate use of IMPALA research by policy-makers and other decision-makers at the regional level, an analysis of regional lung health policies and stakeholders will be undertaken to inform a programmatic strategy for policy engagement. Methods and analysis This analysis will be conducted in three phases. The first phase will be a rapid desk review of regional lung health policies and stakeholders that seeks to understand the regional lung health policy landscape, which issues are prioritised in existing regional policy, key regional actors, and opportunities for engagement with key stakeholders. The second phase will be a rapid desk review of the scientific literature, expanding on the work in the first phase by looking at the external factors that influence regional lung health policy, the ways in which regional bodies influence policy at the national level, investments in lung health, structures for discussion and advocacy, and the role of evidence at the regional level. The third phase will involve a survey of IMPALA partners and researchers as well as interviews with key regional stakeholders to further shed light on regional policies, including policy priorities and gaps, policy implementation status and challenges, stakeholders, and platforms for engagement and promoting uptake of evidence. Discussion Health policy analysis provides insights into power dynamics and the political nature of the prioritisation of health issues, which are often overlooked. In order to ensure the uptake of new knowledge and evidence generated by IMPALA, it is important to consider these complex factors.